A selective insecticidal protein from Pseudomonas mosselii for corn rootworm control. Issue 2 (1st October 2017) - Wei, Jun‐Zhi; O'Rear, Jessica; Schellenberger, Ute; Rosen, Barbara A.; Park, Young‐Jun; McDonald, Mark J.; Zhu, Genhai; Xie, Weiping; Kassa, Adane; Procyk, Lisa; Perez Ortega, Claudia; Zhao, Jian‐Zhou; et al.
Summary: The coleopteran insect western corn rootworm (WCR, Diabrotica virgifera virgifera ) is an economically important pest in North America and Europe. Transgenic corn plants producing Bacillus thuringiensis ( Bt) insecticidal proteins have been useful against this devastating pest, but evolution of resistance has reduced their efficacy. Here, we report the discovery of a novel insecticidal protein, PIP‐47Aa, from an isolate of Pseudomonas mosselii . PIP‐47Aa sequence shows no shared motifs, domains or signatures with other known proteins. Recombinant PIP‐47Aa kills WCR, two other corn rootworm pests ( Diabrotica barberi and Diabrotica undecimpunctata howardi ) and two other beetle species ( Diabrotica speciosa and Phyllotreta cruciferae ), but it was not toxic to the spotted lady beetle ( Coleomegilla maculata ) or seven species of Lepidoptera and Hemiptera. Transgenic corn plants expressing PIP‐47Aa show significant protection from root damage by WCR. PIP‐47Aa kills a WCR strain resistant to mCry3A and does not share rootworm midgut binding sites with mCry3A or AfIP‐1A/1B from Alcaligenes that acts like Cry34Ab1/Cry35Ab1. Our results indicate that PIP‐47Aa is a novel insecticidal protein for controlling the corn rootworm pests.